Perancangan Sistem SISCA Berbasis Website untuk Pengecekan Alat Darurat di PT Aisin Indonesia - Umar Maulana; Muslih Muslih; Novia Wahyu Wulansari (Fakultas Ilmu Komputer, Universitas Dian Nuswantoro, 2026)
This study aims to design and develop a web-based System Information Safety Checksheet Aisin (SISCA) to support the digital, structured, and monitorable inspection process of occupational safety emergency equipment at PT Aisin Indonesia. The system development method applies the Systems Development Life Cycle (SDLC), consisting of planning, requirements analysis, design, implementation, testing, and maintenance. The system was developed using the Laravel framework with Model-View-Controller (MVC) architecture and MySQL database. The main features include role-based user authentication, QR Code scanning, inspection data entry, photo evidence upload, real-time monitoring dashboard, inspection history, and automatic report generation. The Black Box Testing results on 12 main functional scenarios show that all scenarios worked according to the requirements with a success rate of 100%. White Box Testing on the login, equipment inspection, and report generation modules resulted in cyclomatic complexity values of 3, 4, and 3, respectively. These results indicate that SISCA provides functions that meet user requirements, has simple program logic, and improves the effectiveness of inspection documentation, accelerates report access, and reduces the risk of human error.